Pharmacophore-based virtual screening for identifying β5 subunit inhibitor of 20S proteasome. (December 2018) - Arba, Muhammad; Nur-Hidayat, Andry; Surantaadmaja, Slamet Ibrahim; Tjahjono, Daryono H.
Graphical abstract: Lig1546/ZINC33356235 in the binding pocket of β5 subunit of 20S proteasome. Highlights: A pharmacophore-based virtual screening and molecular docking were employed to identify ligands as inhibitors of proteasome β5 subunit. The 40 ns MD simulation and prediction of binding free energy were carried out. The predicted binding potentials of most ligands were better than that of the potential inhibitor, HU10. Abstract: Proteasomal system plays an important role in maintaining cell homeostatis. Overexpression of proteasomes leads to several major diseases, such as cancer and autoimmune disorder. The β5 subunit of proteasome is a crucial active site in proteolysis, and targeting proteasome β5 subunit is essential for proteasome inhibition. In the present study, a pharmacophore-based virtual screening and molecular docking were employed to identify ligands as inhibitors of β5 subunit of proteasome. The pharmacophore features were built with one hydrogen bond donor, two hydrogen bond acceptors, and one hydrophobic feature using native ligand of proteasome (HU10), which was then used to screen ZINC database using ZINCPharmer. The retrieved virtual hits were subjected to molecular docking analysis using iDock. The best six hits were subjected to molecular dynamics (MD) simulation and each complex was stable during 40 ns MD simulation as indicated by root-mean-square-deviation (RMSD) and root-mean-square-fluctuation (RMSF) values. The current study identifies 5 best hits having better binding potentials than HU10 as predicted by molecular mechanics Poisson-Boltzmann Surface Area (MM-PBSA) method, i.e. Lig1540/ZINC33356240, Lig1546/ZINC33356235, Lig1522/ZINC20854878, Lig980/ZINC12391945, and Lig1119/ZINC19865241, which can be used in the development of new proteasome inhibitors.